Physical and mechanical characterization of cement-mortars internally cured with hybrid nanocomposites based on hydrogel and nanoclay - Watanuki Filho, Adhemar (2021)
Cement-based materials are the most produced in civil construction due to their versatility and durability. However, new admixtures have been widely studied and applied for better performance, especially when it comes to curing processes. The hybrid nanocomposite hydrogels, characterized by their hydrophilic characteristics of water absorption and release, stand out as promising agents for internal curing in cementitious matrices. This study proposed to analyze the physical, chemical, and morphological properties of hydrogels based on polyacrylamide, carboxymethylcellulose, and three different concentrations of Cloisite Na+ in two different swelling media (distilled water and filtered solution of water+Portland cement) and to evaluate the effect of applying 0.5% (wt/wtcement) of these presoaked hydrogels on the fresh and hardened state properties of cementitious mortars (1:2.16 and 0.40 w/c ratio). The results showed that the hydrogels provided reductions in slump flow of up to 4.8% for AHN20 mortars and exudation rate for the fresh state. These observations allowed us to evaluate that the increased concentration of nanoclay in the polymer interferes directly in the kinetic parameters of hydrogels and contributes to greater water retention, which may reflect better hydration and reduction of pathologies. As for the results in the hardened state, it was possible to evaluate that the type of curing of the samples was an important factor since there were no variations in densities (2.18+0.02 g/cm³) of all samples, indicating that the hydrogels were partially or fully swollen during the tests. Loss of mechanical strength was observed, but at 28 days for AHN20 mortars, the results were similar to the control, which corroborates the percentage of voids found. In this case, both mortars had a lower rate of voids when compared to AHN0 and AHN10 mortars and consequently better performances in their mechanical properties. The concentration of nanoclay in the hydrogel controls water release, as observed from the results of mass loss and plastic shrinkage that reduced as this concentration increased. The SEM images allowed us to evaluate that the more uniform matrices with higher mechanical properties, with few pores or micro-cracks. It is concluded that hybrid hydrogel nanocomposites can be applied as internal curing agents, especially those produced with 20% (wt/wt of CMC+AAm) nanoclay. Because its more controlled release allowed reducing porosity, water absorption, shrinkage, and significantly acting on the mechanical properties thus, this type of polymeric additive can be an innovative material for water control improvements in cementitious materials technology.